An Old French Trilogy : Texts from the William of Orange Cycle - Whalen, Logan E.; Kibler, William W., 1942-; Jones, Catherine M. (Catherine Mary), 1956- (Book collections on Project MUSE., 2020)
"This volume offers a broad and rich view of the tradition of Old French epic poetry, or chansons de geste, by providing an updated English translation of three central poems from the twelfth-century Guillaume d'Orange cycle"--